Repeatability of Egg Number and Egg Weight in Two Strains of Layer Type Chicken - Udeh, I. (International Journal of Poultry Science, 2010)
The daily egg production records obtained from two strains of layer type chicken for a period of 16 weeks were used to estimate the repeatability of egg number and egg weight in this population. There were 50 pullets for each strain. The pullets were housed in single bird cages and monitored for egg number and egg weight. The egg numbers were summarized on monthly basis for four months while egg weights were recorded at first egg, 30 and 40 weeks respectively. The results indicate that the repeatability estimates for monthly egg numbers ranged from 0.12-0.85 in strain 1 and 0.05-0.62 in strain 2. The repeatability estimates for egg numbers for the four months taken together were low in strain 1 (R = 0.17) and strain 2 (R = 0.07). The repeatability estimates for weight of first egg, egg weight at 30 and 40 weeks were generally low in the two strains of chicken and ranged from 0.04-0.19. The only exception was egg weight at 40 weeks in strain I (R = 0.44). The low repeatability estimates recorded for most of the traits imply that collection of additional records and improvement of non genetic factors influencing egg production will improve the accuracy of characterizing the inherent transmitting ability of the birds in these traits.